Unknown Petr Gzell: Some notes on the one of the authors of the first Czech grammar - Peluněk, F. Lukáš (Bohemica Olomucensia, 2014)
Petr Gzell is the personality which is known and unknown simultaneously. In the scholarly world he is well-known as one of the authors who wrote the first Czech grammar which was published in 1533 in Náměšť nad Oslavou, Western Moravia. Unfortunately, the life story of Petr Gzell is not exact nowadays. This short article deals with the current knowledge about Gzell's life and also challenges the other scholars to make more detailed work about life and work of Petr Gzell, who is definitely very important personality of the Czech and Moravian history.
Keywords: Petr Gzell; Czech grammar